2019
DOI: 10.3390/w11112334
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude and Frequency of Temperature and Precipitation Extremes and the Associated Atmospheric Circulation Patterns in the Yellow River Basin (1960–2017), China

Abstract: Since there are many destructive effects caused by extreme climate events in the Yellow River, it is of great theoretical and practical significance to explore the variations of climatic extremes in this key basin. We used a meteorological dataset from 66 stations within the Yellow River basin (YRB) for the period 1960–2017 to calculate magnitude and frequency of precipitation/temperature extremes. We also analyzed the relationships between the main large-scale atmospheric circulation patterns (ACPs) and preci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…In the present study, the strengths of the trends for the temperature indices were lower than those in the Loess Plateau of northwestern China (Sun et al ., 2016), the Xinjiang Autonomous Region of northwestern China (Wang et al ., 2013a), and the Tibetan Plateau of western China (Wang et al ., 2013b), but greater than those for the Yunnan–Guizhou plateau in southwestern China (Li et al ., 2012) and the Yangtze River basin in central and southern China (Wang et al ., 2014). Specifically, the magnitude of the trend for TNn in mainland China was lower than the average value for the Yangtze River Basin (0.42°C·decade −1 ; Guan et al ., 2015), the Yellow River Basin (0.45°C·decade −1 ; Dong et al ., 2019) and the Yarlung Tsangpo River Basin in China (0.48°C·decade −1 ; Liu et al ., 2019). Similarly, the trend for FD (−2.63 days·decade −1 ) was less than that in the Yellow River Basin (−3.72 days·decade −1 ; Dong et al ., 2019), Tibetan Plateau (−5.69 days·decade −1 ; Sun et al ., 2016), Loess Plateau (−3.22 days·decade −1 ; Wang et al ., 2013b), and Yarlung Tsangpo River Basin (−4.39 days·decade −1 ; Liu et al ., 2019), but larger than those in the Wujiang River Basin (−2.19 days·decade −1 ) and Jialing River Basin (−1.93 days·decade −1 ) (Wang et al ., 2014) in China.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, the strengths of the trends for the temperature indices were lower than those in the Loess Plateau of northwestern China (Sun et al ., 2016), the Xinjiang Autonomous Region of northwestern China (Wang et al ., 2013a), and the Tibetan Plateau of western China (Wang et al ., 2013b), but greater than those for the Yunnan–Guizhou plateau in southwestern China (Li et al ., 2012) and the Yangtze River basin in central and southern China (Wang et al ., 2014). Specifically, the magnitude of the trend for TNn in mainland China was lower than the average value for the Yangtze River Basin (0.42°C·decade −1 ; Guan et al ., 2015), the Yellow River Basin (0.45°C·decade −1 ; Dong et al ., 2019) and the Yarlung Tsangpo River Basin in China (0.48°C·decade −1 ; Liu et al ., 2019). Similarly, the trend for FD (−2.63 days·decade −1 ) was less than that in the Yellow River Basin (−3.72 days·decade −1 ; Dong et al ., 2019), Tibetan Plateau (−5.69 days·decade −1 ; Sun et al ., 2016), Loess Plateau (−3.22 days·decade −1 ; Wang et al ., 2013b), and Yarlung Tsangpo River Basin (−4.39 days·decade −1 ; Liu et al ., 2019), but larger than those in the Wujiang River Basin (−2.19 days·decade −1 ) and Jialing River Basin (−1.93 days·decade −1 ) (Wang et al ., 2014) in China.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the magnitude of the trend for TNn in mainland China was lower than the average value for the Yangtze River Basin (0.42°C·decade −1 ; Guan et al ., 2015), the Yellow River Basin (0.45°C·decade −1 ; Dong et al ., 2019) and the Yarlung Tsangpo River Basin in China (0.48°C·decade −1 ; Liu et al ., 2019). Similarly, the trend for FD (−2.63 days·decade −1 ) was less than that in the Yellow River Basin (−3.72 days·decade −1 ; Dong et al ., 2019), Tibetan Plateau (−5.69 days·decade −1 ; Sun et al ., 2016), Loess Plateau (−3.22 days·decade −1 ; Wang et al ., 2013b), and Yarlung Tsangpo River Basin (−4.39 days·decade −1 ; Liu et al ., 2019), but larger than those in the Wujiang River Basin (−2.19 days·decade −1 ) and Jialing River Basin (−1.93 days·decade −1 ) (Wang et al ., 2014) in China.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Bayazit and Önöz (2007) concluded that such serial correlations have negligible effects on the detection of significant trends in data sets with large samples ( n ≥ 50), like the time series employed by the present study. Both TFPW and RB methods have already been applied by previous studies for exploring variability and trends in extreme precipitation indices in different parts of the world (e.g., Irannezhad et al ., 2016; Dong et al ., 2019).…”
Section: Methodsmentioning
confidence: 99%
“…To account for their confounding effects, natural variability modes are considered in our analysis. Modes like the Atlantic multidecadal oscillation (AMO), the Pacific decadal oscillation (PDO), the Southern Oscillation index (SOI), the northern annular mode (NAM), and the North Atlantic Oscillation (NAO) have a stronger influence in the NH regions (Hu et al 2003;Englehart and Douglas 2004;Brönnimann et al 2007;Riaz et al 2017;Brunetti and Kutiel 2011;de Beurs et al 2018;Dong et al 2019). The dipole mode index or Indian Ocean dipole (IOD), southern annular mode (SAM), North Pacific index (NPI), AMO, and SOI influence SH regions (Mason and Jury 1997;Power et al 1999;Tyson and Preston-Whyte 2000;Hendon et al 2007;Fogt et al 2011;Ashcroft et al 2014;Lakhraj-Govender and Grab 2018).…”
Section: A Observational Data and Spatial Domainsmentioning
confidence: 99%